The enchanted bridge - Elliott, Zetta (Elliott, Zetta. Dragons in a bag (Series), 2023)
"Jaxon and his friends are back in the magical realm, Palmera, trying to convince Guardian Sis that magical creatures should exist in both world, but things might be even more complicated than Jax and his friends realize"--